The Relationship Between Serum Delta FSH Level and Ovarian Response in IVF/ICSI Cycles - Hu, Linli; Sun, Bo; Ma, Yujia; Li, Lu; Wang, Fang; Shi, Hao; Sun, Yingpu (Frontiers in Endocrinology, 2020)
Backgruond: When ovarian response to FSH stimulation for IVF/ICSI is unsatisfactory, the FSH dose is often adjusted in the treatment cycles, thereby assuming that hormone status and follicular development were insufficient for optimal stimulation. Objectives: To evaluate whether serum delta FSH levels between D6 of gonadotrophin and basal serum FSH or between D6 of gonadotrophin and D1 of gonadotrophin predict ovarian response in IVF/ICSI cycles. Method: This study was conducted at the Reproductive Medicine, The First Affiliated Hospital of Zhengzhou University between August 2015 and December 2017 (n =3109). Delta FSH1:Serum delta FSH1 levels between D6 of gonadotrophin and basal serum FSH. Delta FSH2: Serum delta FSH2 levels between D6 of gonadotrophin and D1 of gonadotrophin. Logistic regression was used to analyze the association between Delta FSH1 level and delta FSH2 level and ovarian response. Results: Part I: Delta FSH1 levels (mean: 1.41±3.46) in normal responders were higher than delta FSH1 levels (mean: 1.07±23.89) in hyper responders (P= 0.0248). The tertile of delta FSH1 is dif<=0, 0